FINANCIAL AND NON-FINANCIAL FACTORS AFFECTING GOING CONCERN AUDIT OPINION ON MANUFACTURING COMPANIES LISTED IN IDX 2012-2014 - admin, Yvonne Tamara B42112004 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
Auditor’s judgment becomes a major attention of financial users to take further decision. Financial users such as investors, creditors, and others, rely heavily on the information provided in the financial statement to assess and identify the company’s strength and weaknesses. This is a cross sectional studies, involving 110 manufacturing companies that listed in Indonesia Stock Exchange from 2012-2014 with total data of 330 obtained from financial statement and annual reports. The data analysis methods used were Chi-Square Test, Pearson Product Moment Correlation and Binary Logistic Regression Test. From binary logistic regression, financial performance (p<0.05) and presence of evidence (p<0.05) were associated with the higher probability of issuance of going concern audit opinion. The result also shows that audit fee has no significant effect towards issuance of going concern audit opinion. Keywords: financial performance, audit evidence, audit fees, disclosures, going concern audit opinion.